Anatomical, Physical and Mechanical Properties of Aerial Roots of Ficus bengalensis L. (Thandlu) - Shukla, S. R.; Sujatha, M.; Sivaram Prasad, N. V. (Indian Forester, 2019)
This study reports on radial variations of anatomical parameters of aerial roots Ficus bengalensis (Thandlu) such as fibre length, fibre diameter, fibre lumen diameter, fibre wall thickness, vessel element length, vessel diameter and vessel frequency. Certain important physical and mechanical properties of Thandlu wood such as equilibrium moisture content (EMC), specific gravity, density, flexural strength (modulus of rupture-MOR), flexural stiffness (modulus of elasticity-MOE), compressive strength parallel to grain (maximum compressive stress-MCS), compressive strength perpendicular to grain and surface hardness were also investigated. Average air-dry density of Thandlu wood was found to be 537.6 Â± 91.4 kg/m3. Moreover, specific gravity exhibited increasing trend from pith to periphery and average values were found to be correlated with anatomical properties. Radial variations of anatomical parameters were observed to be significant. Fibre lumen diameter was negatively correlated while fibre wall thickness was positively correlated with density. Similarly, vessel element length was positively correlated with fibre length and fibre lumen diameter was found to be positively correlated with the fibre diameter. The physical and mechanical properties in air-dry condition of Thandlu wood were compared with Tectona grandis (Teak) wood. Naturally having long cylindrical shape, light to moderately heavy wood and moderate to strong mechanical parameters of Thandlu in dry condition, their traditional applications in different areas are well supported by the observations made in the present study.